Vegetation dynamics and its response to climate change during the past 2000 years along the Amur River Basin, Northeast China. (October 2020) - Han, Dongxue; Gao, Chuanyu; Liu, Hanxiang; Yu, Xiaofei; Li, Yunhui; Cong, Jinxin; Wang, Guoping
Highlights: There was a synchrony of vegetation change along the river basin in late Holocene. Human impact occurred earlier in the Plain than the areal Mountains along the basin. Human activity became main factor influencing vegetation variation at 150 cal yr BP. Vegetation composition can be used to reconstruct climate before human disturbance. Abstract: The Amur River Basin is located in high latitudes, which is sensitive to the global climate change. However, only a few previous studies have tried to study the climate change in this region. To better understand the historical variation of vegetation and climate during the past 2000 years, we present a new palynological data from the Lesser Khingan Mountains, and compared the vegetation change along the Amur River Basin. It was possible to reconstruct climate based on vegetation composition before human disturbance. The results show that: the climate was moderately cold and humid during the 2000 to 700 cal yr BP, and the vegetation was mainly coniferous and broad-leaved mixed forest, and the abundance of Cyperaceae was relatively high. After that, the temperature and humidity declined, corresponding to the Little Ice Age. And the vegetation types also obviously changed that the conifers expanded, and the contents of broad-leaved trees and herbaceous Cyperaceae decreased. Since about 150 cal yr BP, the climate tended to be warm which belonged to Current Warm Period, and the main vegetation type was the secondary forests. The spread of the Han farming culture accompanied by the territorial expansion of the Tang Dynasty to the Sanjiang Plain at around 1300 cal yr BP caused human disturbance occurred earlier in the Sanjiang Plain than the Greater and Lesser Khingan Mountains. Additionally, the anthropogenic activities obviously intensified during the past hundred years along the Amur River Basin.